Diagnostic performance of lactate dehydrogenase (LDH) isoenzymes levels for multi-organ damage and in patients with COVID-19: LDH isoenzyme levels in COVID-19 - Ergenç, İlkay (Journal of Medical Biochemistry, 2022)
Introduction: Lactate dehydrogenase (LDH) levels are predictive of coronavirus disease 2019 (COVID-19) severity. We investigated LDH isoenzyme levels to identify the tissue responsible for serum LDH elevation in patients with COVID-19.Materials and Methods: Hospitalised COVID-19 patients with serum LDH levels exceeding the upper limit of normal were included. LDH isoenzymes were detected quantitatively on agarose gels. The radiological severity of lung involvement on computed tomography was scored as 0–5 for each lobe (total possible score, 0–25). Disease severity was determined using the World Health Organization (WHO) clinical progression scale.Results: In total, 111 patients (mean age, 59.96 ± 16.14), including 43 females (38.7%), were enrolled. The serum levels of total LDH and all five LDH isoenzymes were significantly higher in the severe group. The levels of all LDH isoenzymes excluding LDH5 positively correlated with the WHO score. LDH3 levels correlated with chest computed tomography findings (r2 = 0.267, p = 0.005). On multivariate analysis, LDH3 was an independent risk factor for the deterioration of COVID-19. Discussion: LDH3 appears to be an independent risk factor for deterioration in patients with COVID-19. LDH elevation in patients with COVID-19 predominantly resulted from lung, liver and muscle damage.
Keywords: Coronavirus; COVID-19; Lactate dehydrogenase; LDH isoenzymes